Pre-hypertension independent deleterious effects in Body system - Khatri Sapkota, Niraj (Innovare Journal of Medical Sciences, 2017)
Abstract There is clear indication that prehypertension is the state of Â persistent blood pressure of being (120-139 mmHg/80-89 mmHg) Â or named Â pseudohypertensionis Â is a significant marker that certainly progresses to develop incident hypertension >140-159/ 80-89 Â that causes cardiovascular risk. Therefore it became Â essential to prevent this progression Â so that incident hypertension be precluded but it is brainy if we research on the independent harmful effects of this pre-hypertension on the body system and Â therefore be aware of Â possible Â interventional impingement salvage Â effectively to the body system in the absence of cardiovascular or other secondary disease. This miniri reveiw will focus independent deleterious effect of prehypertension in the body system architectural and functioning, in the absence of co-morbid state. key words.: Prehypertension,Cardiovascucar risk ,Indepedent effect. Â Â